Mechanisms of water-inrush mitigation under alternative grouting strategies during shaft sinking: Solidification-enabled stress–seepage–damage coupling - Wenxin Li; Dan Ma; Jiangyu Wu; Xuefeng Gao; Qiang Li; Changle Xu; Chuanjiu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

The Roles of SOCS in Teleost Immunity: Cytokine Regulation and Host Defense - Ying Zhang; Li Yang; Xiuying Cui; Feng Gao; Yanjing Zhao; Xianghui Kong (Reviews in Aquaculture, 2026)
The Suppressor of Cytokine Signaling (SOCS) family comprises key regulatory molecules which are essential for maintaining immune homeostasis in vertebrates. Owing to a teleost‐specific whole‐genome duplication event, SOCS family members exhibit higher diversity and significant functional differentiation, forming a complex and precise immune regulatory network. This review comprehensively summarizes the current understanding of SOCS‐mediated cytokine regulation and host defense mechanisms in teleosts. SOCS proteins, particularly SOCS1 and SOCS3, exert dual regulatory effects in antiviral and antibacterial immunity as well as in inflammatory balance by negatively modulating key pathways such as JAK/STAT and NF‐κB, exemplifying their “double‐edged sword” role. Moreover, we provide the first comprehensive synthesis of environmental regulation of SOCS expression in teleosts, integrating emerging evidence on how to modulate SOCS levels after temperature stress, neuroendocrine activation via cortisol, hypoxia, and chemical pollutants and how to link environmental conditions to immune competence. This environmental perspective supplies direct implications for understanding stress‐induced immunosuppression in aquaculture. Finally, we discuss the potential application of targeting SOCS signaling in aquaculture practices, including applications in disease‐resistant breeding, vaccine development, and immunostimulant design. In‐depth understanding of SOCS diversity and function in fish will provide novel molecular insights and innovative strategies for precise disease control and sustainable aquaculture.

Breaking the legume intensification paradox: Precision nitrogen-phosphorus fertilization for optimizing biological nitrogen fixation, yield, and soil physicochemical properties in mung bean - Jiahao Ge; Qi Wang; Enlei Li; Siyuan Zhang; Xaioyi Han; Shaofei Li; Qixuan Wang; Qingming Wang; Pengyue Wu; Feng Gao; Baili Feng; Jinfeng Gao (Applied Soil Ecology, 2025)

Silver nanoparticles altered soil respiration, enzyme activity, carbon use efficiency and microbial community in an upland soil - Xincheng Hong; Yudi Song; Dongdong Cao; Shengwen Xu; Feng Gao; Haoxin Fan; Huaiying Yao (Applied Soil Ecology, 2025)

Microbial community assembly elucidates differential biotic homogenization in soils caused by agricultural expansion in the Yangtze River estuary - Yufan Yang; Yanhan Ji; Shuying Wang; Congrui Liu; Ping Zhang; Guifeng Gao; Yu Shi; Jiandong Jiang; Xu Liu; Baozhan Wang (Applied Soil Ecology, 2025)

The role of fungal keystone taxa in soil multifunctionality across subtropical forests - Huaxiang Wang; Shuoxing Wei; Zhihui Wang; Dian Tian; Zhifeng Lu; Hanbiao Ou; Feng Gao; Shiqi Ren; Lijun Chen (Applied Soil Ecology, 2025)

Geographical and environmental drivers of ureolytic microbial communities and their roles in nitrogen cycling under fertilization - Haoxin Fan; Ziqi Su; Xincheng Hong; Feng Gao; Huaiying Yao (Applied Soil Ecology, 2025)

Plant richness reshuffles the soil microbiome in permafrost ecosystems - Zhong-Miao Liu; Gui-Feng Gao; Nai-Li Zhang; Hai-Yan Chu; Xiang-Yun Zhu (Applied Soil Ecology, 2025)

Benefit and risk: Keystone biomes in maize rhizosphere associated with crop yield under different fertilizations - Xiyuan Xu; Kunkun Fan; Qi Li; Teng Yang; Gui-Feng Gao; Yuying Ma; Li Nie; Wenju Liang; Jiabao Zhang; Haiyan Chu (Applied Soil Ecology, 2024)

Signalling regulation of reactive oxygen species in fish inflammation - Feng Gao; Yanjing Zhao; Xiaowei Shi; Dan Qiao; Chao Pei; Xianghui Kong (Reviews in Aquaculture, 2024)
Reactive oxygen species (ROS), which are key cellular signalling molecules, are reactive chemicals containing oxygen. Cell survival or death is a critical issue in the inflammatory response. Accumulation of ROS involves ROS generation and scavenging, which determine ROS homeostasis. Understanding the roles of ROS in modulating the inflammatory response in fish is vital for helping protect fish from the damage of water pollutants in harsh environmental conditions. ROS‐related key genes and signalling pathways are relatively conserved in fish but vary among different species. Recent frequent incidences of fish diseases have posed a considerable challenge to large‐scale aquaculture. ROS is important in stress perception, integration of diverse stress‐responsive signalling networks, and activation of animal defence mechanisms, which frequently occur during inflammation in fish. This review summarises recent studies on ROS signalling pathways during inflammation in fish. Furthermore, it examines the relationship between ROS and inflammation in fish. This review may contribute to the understanding of the underlying mechanisms by which ROS regulate inflammation in fish and provide suggestions for sustainable development in aquaculture.

The role of ferroptosis in fish inflammation - Feng Gao; Xiaowei Shi; Chao Pei; Xianliang Zhao; Lei Zhu; Jie Zhang; Li Li; Chen Li; Xianghui Kong (Reviews in Aquaculture, 2023)
Ferroptosis, as one of cell death modalities, is driven by iron‐dependent phospholipid peroxidation and regulated by various cellular metabolic pathways, including iron, amino acid and lipid metabolism, as well as disease‐related signalling pathways. Cell survival or death is a critical issue in the inflammatory response. On the one hand, ferroptosis is more immunogenic than apoptosis, and ruptured ferroptotic cells release damage‐associated molecular patterns (DAMPs), which can trigger an inflammatory response. On the other hand, various pathogenic bacteria may cause peroxidation of polyunsaturated fatty acids (PUFAs) on the cell membrane, leading to ferroptosis. In fish, the key genes and signalling pathways related to ferroptosis are conserved, but there are still differences among fish species. In recent years, frequent occurrences of fish diseases have posed a considerable challenge to the large‐scale aquaculture. The specific precursors for ferroptotic cell death were iron‐dependent oxidative stress and lipid peroxidation, which always occur in fish inflammation. This review summarizes recent studies on ferroptosis in fish inflammation, that is, iron‐dependent programmed cell death, to address ferroptosis, inflammation and correlations between them in fish. This review may contribute to a better understanding of the underlying mechanisms of ferroptosis and inflammation in fish and provides suggestions for sustainable development and large‐scale aquaculture farming.

Current progress in the authentication of fishery and aquatic products using multi‐element and stable isotope analyses combined with chemometrics - Cui Han; Li Li; Xuan Dong; Qinfeng Gao; Shuanglin Dong (Reviews in Aquaculture, 2022)
Fraud occurs frequently in the fishery and aquatic product markets. Therefore, the authentication of fishery and aquatic products has become a crucial issue. Recently, elemental and stable isotope analyses have become popular for aquatic food authentication. In this review, relevant literature was collected to highlight the current progress in the authentication of fishery and aquatic products using multi‐element and stable isotope analyses combined with chemometrics. Both technologies provide valuable insight regarding geographic origin, culture method, and species identification of fishery and aquatic products. Their classification rate varied from 60% to 100% in most studies. The formation of both elemental and stable isotope profiles of fishery and aquatic products is complex and affected by many factors, including diet, biological differences, and culture environment. The classification rate of these methods may be increased by combining multiple technologies, selecting the correct elements and stable isotopes for specific purposes, selecting and verifying proper discrimination methods, and increasing sample sizes. This review provides valuable information to build reliable and stable tracing methods for fishery and aquatic products.

Deep learning for smart fish farming: applications, opportunities and challenges - Xinting Yang; Song Zhang; Jintao Liu; Qinfeng Gao; Shuanglin Dong; Chao Zhou (Reviews in Aquaculture, 2021)
The rapid emergence of deep learning (DL) technology has resulted in its successful use in various fields, including aquaculture. DL creates both new opportunities and a series of challenges for information and data processing in smart fish farming. This paper focuses on applications of DL in aquaculture, including live fish identification, species classification, behavioural analysis, feeding decisions, size or biomass estimation, and water quality prediction. The technical details of DL methods applied to smart fish farming are also analysed, including data, algorithms and performance. The review results show that the most significant contribution of DL is its ability to automatically extract features. However, challenges still exist; DL is still in a weak artificial intelligence stage and requires large amounts of labelled data for training, which has become a bottleneck that restricts further DL applications in aquaculture. Nevertheless, DL still offers breakthroughs for addressing complex data in aquaculture. In brief, our purpose is to provide researchers and practitioners with a better understanding of the current state of the art of DL in aquaculture, which can provide strong support for implementing smart fish farming applications.

A comparison of factors influencing the summer phytoplankton biomass in China’s three largest freshwater lakes: Poyang, Dongting, and Taihu - Xia Liu; Kuimei Qian; Yuwei Chen; Junfeng Gao (Hydrobiologia, 2017)

Cyanobacteria in the complex river-connected Poyang Lake: horizontal distribution and transport - Xia Liu; Yun-Liang Li; Bao-Gui Liu; Kui-Mei Qian; Yu-Wei Chen; Jun-Feng Gao (Hydrobiologia, 2016)